DINAMIKA SIBLING RIVALRY PERILAKU SOSIAL PADA ANAK USIA DINI DALAM KONTEKS KELUARGA DENGAN PERBEDAAN JARAK USIA SAUDARA: PENDEKATAN STUDI KASUS (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Sibling rivalry is a common phenomenon in families with more than one child and can influence early childhood social development. This study aims to describe the dynamics of sibling rivalry and its implications for early childhood social behavior within a family context characterized by age differences between siblings. This research employed a qualitative approach using a single case study design involving a nuclear family with two daughters aged 8 and 5 years. Data were collected through participatory observation, in-depth interviews with parents, and documentation related to the children’s social development. The data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing, while data validity was ensured through technique triangulation. The findings reveal that sibling rivalry appears in the form of competition for parental attention, verbal conflicts during play, and jealousy over ownership of objects. The age gap influences interaction patterns, where the older child tends to be more dominant, while the younger child shows more intense emotional responses. The study concludes that sibling rivalry is not always negative, but can serve as a medium for social learning when managed through responsive parenting and appropriate guidance